Relationship Between Environmental Management Policy and the Local Wisdom of Indigenous Peoples in the Handling of COVID-19 in Indonesia - Wahyu Nugroho (Oñati Socio-Legal Series)
This paper aims to understand the concept of local wisdom (Indonesian term: kearifan local) from the perspective of Indonesian indigenous peoples (Indonesian term: masyarakat adat) in handling COVID-19 and environmental management policies. In this article, use normative legal research methods, empirical data based on developments in policy and media in Indonesia, and qualitative analysis. The findings of this study are first, constructing local wisdom of Indonesian indigenous peoples in environmental management and handling of COVID-19, based on the teachings of their ancestors and based on the customary calendar as a reference; second, build partnerships related to environmental policies and indigenous peoples by considering the balance of nature and changes in human behavior through local wisdom to reduce carbon emissions during a pandemic. The author is interested in this research because there is an integration of local wisdom of Indonesian indigenous peoples in environmental policies and handling COVID-19.